Allergenicity and toxicology of inhaled silver nanoparticles in allergen-provocation mice models - Chuang HC (Dove Medical Press, 2013)
Hsiao-Chi Chuang,1,2,* Ta-Chih Hsiao,3,* Cheng-Kuan Wu,4 Hui-Hsien Chang,5 Chii-Hong Lee,6 Chih-Cheng Chang,1,2 Tsun-Jen Cheng4,7 On behalf of the Taiwan CardioPulmonary Research Group (T-CPR) 1School of Respiratory Therapy, College of Medicine, 2Division of Pulmonary Medicine, Department of Internal Medicine, Shuang Ho Hospital, Taipei Medical University, Taipei, 3Graduate Institute of Environmental Engineering, National Central University, Taoyuan, 4Institute of Occupational Medicine and Industrial Hygiene, College of Public Health, National Taiwan University, Taipei, 5Institute of Environmental Health, College of Public Health, National Taiwan University, 6Department of Pathology, Shuang Ho Hospital, Taipei Medical University, Taipei, 7Department of Public Health, College of Public Health, National Taiwan University, Taipei, Taiwan *These authors contributed equally to this work Abstract: Silver nanoparticles (AgNP) have been associated with the exacerbation of airway hyperresponsiveness. However, the allergenicity and toxicology of AgNP in healthy and allergic individuals are unclear. We investigated the pathophysiological responses to AgNP inhalation in a murine model of asthma. Continuous and stable levels of 33 nm AgNP were maintained at 3.3 mg/m3 during the experimental period. AgNP exposure concomitant with ovalbumin challenge increased the enhanced pause (Penh) in the control and allergic groups. AgNP evoked neutrophil, lymphocyte and eosinophil infiltration into the airways and elevated the levels of allergic markers (immunoglobulin E [IgE] and leukotriene E4 [LTE4]), the type 2 T helper (Th2) cytokine interleukin-13 (IL-13), and oxidative stress (8-hydroxy-2′-deoxyguanosine [8-OHdG]) in healthy and allergic mice. Bronchocentric interstitial inflammation was observed after AgNP inhalation. After inhalation, the AgNP accumulated predominantly in the lungs, and trivial amounts of AgNP were excreted in the urine and feces. Furthermore, the AgNP induced inflammatory responses in the peritoneum. The inhalation of AgNP may present safety concerns in healthy and susceptible individuals. Keywords: inductively coupled plasma-mass spectrometry, inflammation, leukotriene E4, ovalbumin, oxidative stress